Talking about health, wellbeing and disability in young people: An Aboriginal perspective - Jalla, Caris Lae (Curtin University, 2016)
Disability in Australian Indigenous populations is twice as high compared to non-Indigenous populations. This study explores the perceptions of health and disability from the viewpoint of Indigenous children and young people with and without disabilities. A total of 24 Perth youths aged 9 to 26 years participated. Findings outline the facilitators and barriers to health and beliefs around the causes of disability. These results have important implications for disability service providers working with Indigenous communities.